Pre- and postpartum metabolizable protein supply: II. Effects on plasma amino acids and markers of tissue mobilization in transition Holstein dairy cows - T.A. Westhoff; T.R. Overton; A.F. Ortega; M.E. Van Amburgh; S. Mann (Journal of Dairy Science)
ABSTRACT: The influence of diet composition on the degree of adipose and lean muscle mobilization and concentrations of circulating AA has been demonstrated during the transition period. Altering the MP supply might offer a strategy to control tissue mobilization and increase circulating AA availability, but the optimum supply of MP fed pre- and postpartum remains unknown. We investigated the effect of increasing the MP supply in the prepartum, postpartum, or both diets on plasma AA concentrations and ultrasound and circulating indicators of tissue mobilization. Multiparous Holstein cows (n = 96) were assigned to 1 of 4 treatment groups at 28 d before expected calving following a randomized block design. Prepartum diets were formulated to contain either a control (CON; 85 g of MP/kg DM; 1,175 g of MP/d) or high (HI; 113 g of MP/kg DM; 1,603 g of MP/d) level of estimated MP. From calving to 21 DIM, fresh diets were formulated to contain either a control (CON; 104 g of MP/kg DM; 2,044 g of MP/d) or high (HI; 131 g of MP/kg DM; 2,685 g of MP/d) level of estimated MP. To control the potential confounding effect of Met and Lys supply, diets were formulated to supply an equal amount at 1.24 and 3.84 g/Mcal of ME in both prepartum diets and 1.15 and 3.16 g/Mcal of ME in both postpartum diets, respectively. The combination of a pre- and postpartum diet resulted in 4 treatment groups: (1) CON-CON (CC; n = 23), (2) CON-HI (CH; n = 24), (3) HI-CON (HC; n = 22), and (4) HI-HI (HH; n = 23). A common lactation diet (113 g of MP/kg DM; 2,956 g of MP/d) was fed from 22 DIM to the end of the observation period at 42 DIM. Transcutaneous ultrasonography was used to determine the longissimus dorsi muscle diameter and backfat thickness. Concentrations of plasma AA, 3-methylhistidine (3MH), and creatinine were determined on a subset of cows (n = 60) using ultra-high-performance liquid chromatography and MS. Treatment did not affect the longissimus dorsi muscle diameter from −14 to 21 d relative to calving, but the diameter was greater in CH compared with HH at 40 DIM. Backfat thickness and the ratio of 3MH to creatinine did not differ by treatment. Concentrations of EAA were greater at −13 d relative to calving in HH compared with CC and CH and at −6 d relative to calving EAA concentrations were higher in HC compared with CC. Cows fed the HI diet postpartum had elevated EAA concentrations at 6 and 20 DIM compared with cows fed the CON postpartum diet but EAA concentration did not differ at 40 DIM. Total NEAA concentrations were higher in CH compared with HC and HH at −6 d relative to calving, but NEAA concentration did not differ by treatment at −13, 6, 20, or 40 d relative to calving. In conclusion, increasing the supply of MP fed prepartum, postpartum, or both had minimal effects on tissue mobilization but influenced concentrations of plasma AA.